PVDF-based coatings with CNT additions for strain monitoring of mortar substrates subjected to bending - Milone Gabriele; Tulliani Jean-Marc; Al-Tabbaa Abir (MATEC Web of Conferences, 2023)
Sensing coatings are rapidly entering the field of non-destructive tests. While cement-based composites are proving an excellent interaction with new/recent structures, polymer-based coatings, already employed for structural retrofitting purposes, can provide a valuable alternative. This study investigated the production, application, and use of poly(vinylidene fluoride) (PVDF) coatings. A 10w/v% PVDF-to-solvent ratio became the best trade-off between electrical conductivity and bond strength with the substrate. Different concentrations of Carbon Nanotubes (CNT) were investigated: 0.05, 0.10, 0.25, 0.50, and 0.75% by weight of PVDF. The conductive PVDF-CNT composites were brushed on the casted mortar beams with screws embedded as electrodes. The mortar beams and attached polymer coatings were then subjected to bending stress. The Gauge Factor was obtained by comparing the substrate’s strain with the coating’s electric response. The sensing intervals in the Fractional Change of Resistance-strain curves varied in relation to the CNT concentration. For instance, adding 0.50w/v% of CNT gave the highest sensitivity up to 0.2‰ strain, followed by a lower – still sufficient – gauge factor. PVDF-based coatings with CNT additions of 0.25 and 0.75w/v% witnessed a comparable sensing performance in the same strain limits, abruptly increasing and finally stabilizing to a low gauge factor. In contrast, both 0.05 and 0.10w/v% resulted in a low monitoring potential overall. The varying sensing zones experienced by the coating were attributed to the microscopical behavior of CNT within the PVDF matrix. In conclusion, the results highlighted the potentiality of polymeric coatings for sensing, monitoring, and inspection of concrete structures.